Building multi-attribute decision model based on Kansei Information in environment with hybrid uncertainty - Junzo Watada, Junzo Watada
The objective of this paper is to build multi attribute decision model considering Kansei information in hybrid uncertain environment. First, fuzzy random variable is explained to deal with the models in hybrid uncertain environment. Section, using fuzzy random variables, linear regression model (FRRM) is formulated. Third, multi-attribute decision model is presented in presence of Kansei information given by experts in an environment with hybrid uncertainty involving both randomness and fuzziness.